EVALUASI IMPLEMENTASI SISTEM INFORMASI MANAJEMEN PUSKESMAS (SIMPUS) TERINTEGRASI DI KULONPROGO YOGYAKARTA - Ahmad Yani Noor, Nurrul Ainy; Nurrul ainy (Jurnal_Kebidanan, 2022)
Kulonprogo was a district that has implemented bridging between SIMPUS Jojok and P-Care, but the implementation were still obstacles. Among them, there were unsynchronized data between SIMPUS Jojok and P-Care and SIMPUS Jojok with SIKDA was not integrated. So that the existing problems do not occur in a prolonged manner, it is better if an evaluation process is better and more transparent by an external (independent) party, and strengthened by using a comprehensive evaluation method. HOT-fit evaluation is a comprehensive method that can be used in evaluating the implementation of SIMPUS in Kulonprogo. In addition, this study aims to determine the extent of implementation of integration in Kulonprogo. The method used in this research is a mix method in which quantitative and qualitative approaches are combined. Data collection was done by means of in-depth interviews (in-depth interviews), questionnaires, and observations. Based on the research results, problems were found in the implementation of SIMPUS from the aspects of Human, Organization, Technology, and Benefits. In addition, the implementation of SIMPUS in Kulonprogo was included in the integrated criteria, but the form of integration that occurred was the linkage integration group (linkage). Linkage integration is included in the integration group that has the lowest position compared to the other 2 integration groups.